PENDEKATAN DESAIN REGENERATIF PADA FASILITAS PENGELOLAAN AIR SEBAGAI URBAN EDU ECO TOURISM DI WADUK SUNTER BARAT - Angelita Natasya; Priscilla Epifania Ariaji (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2026)
West Sunter Reservoir plays a vital role as flood control infrastructure and a blue open space in North Jakarta. However, this area is experiencing significant ecological degradation due to domestic wastewater pollution and urbanization pressures, which limit its function as a provider of clean water and a viable public space. Conventional architectural approaches focusing solely on mitigating negative impacts are deemed insufficient to address the complexity of this ecosystem damage; strategies capable of restoring (regenerating) natural systems while reviving social interactions are required. This research aims to formulate a design for a water management facility based on urban edu-eco tourism by integrating two theoretical approaches: regenerative architecture and landscape urbanism. The research employs a qualitative descriptive method, which includes in-depth site analysis regarding water quality and spatial conditions, literature studies, and design synthesis. The design results demonstrate that regenerative architecture principles can be implemented through building systems that actively purify water using natural technologies such as floating treatment wetlands, constructed wetlands, and green roofs. Meanwhile, the landscape urbanism approach serves to blur the boundaries between building mass and the landscape through organic pedestrian circulation and publicly accessible green roofs. The integration of these two approaches yields a hybrid infrastructure typology that not only restores the water quality of West Sunter Reservoir but also functions as an environmental education facility, strengthening the relationship between urban society and its water ecosystem. Keywords:  landscape urbanism; regenerative architecture; Sunter Barat Reservoir; urban edu-eco tourism; water treatment Abstrak Waduk Sunter Barat memegang peranan vital sebagai infrastruktur pengendali banjir dan ruang terbuka biru di Jakarta Utara. Namun, kawasan ini mengalami degradasi ekologis signifikan akibat pencemaran air limbah domestik dan tekanan urbanisasi yang membatasi fungsinya sebagai penyedia air bersih maupun ruang publik yang layak. Pendekatan arsitektur konvensional yang hanya berfokus pada mitigasi dampak negatif dinilai tidak lagi cukup untuk mengatasi kompleksitas kerusakan ekosistem tersebut; diperlukan strategi yang mampu memulihkan (regenerasi) sistem alam sekaligus menghidupkan kembali interaksi sosial. Penelitian ini bertujuan merumuskan desain fasilitas pengelolaan air berbasis urban edu-eco tourism dengan mengintegrasikan dua pendekatan teoritis: arsitektur regeneratif dan landscape urbanism. Metode penelitian menggunakan deskriptif kualitatif yang meliputi analisis tapak mendalam terhadap kualitas air dan kondisi spasial, studi literatur, serta sintesis desain. Hasil perancangan menunjukkan bahwa prinsip arsitektur regeneratif dapat diimplementasikan melalui sistem bangunan yang bekerja aktif membersihkan air menggunakan teknologi alami seperti floating treatment wetland, constructed wetland, dan green roof. Sementara itu, pendekatan landscape urbanism berperan dalam meleburkan batas antara massa bangunan dan lanskap melalui sirkulasi pedestrian yang organik dan atap hijau yang dapat diakses publik. Integrasi kedua pendekatan ini menghasilkan tipologi bangunan infrastruktur hibrida yang tidak hanya memulihkan kualitas air Waduk Sunter Barat, tetapi juga berfungsi sebagai sarana edukasi lingkungan yang memperkuat hubungan antara masyarakat urban dan ekosistem airnya.